Factors Associated with Failure of Non-invasive Positive Pressure Ventilation in a Critical Care Helicopter Emergency Medical Service. Issue 3 (27th February 2015) - Lee, James S.; O'Dochartaigh, Domhnall; MacKenzie, Mark; Hudson, Darren; Couperthwaite, Stephanie; Villa-Roel, Cristina; Rowe, Brian H.
Abstract: Introduction: Non-invasive positive pressure ventilation (NIPPV) is used to treat severe acute respiratory distress. Prehospital NIPPV has been associated with a reduction in both in-hospital mortality and the need for invasive ventilation. Hypothesis/Problem: The authors of this study examined factors associated with NIPPV failure and evaluated the impact of NIPPV on scene times in a critical care helicopter Emergency Medical Service (HEMS). Non-invasive positive pressure ventilation failure was defined as the need for airway intervention or alternative means of ventilatory support. Methods: A retrospective chart review of consecutive patients where NIPPV was completed in a critical care HEMS was conducted. Factors associated with NIPPV failure in univariate analyses and from published literature were included in a multivariable, logistic regression model. Results: From a total of 44 patients, NIPPV failed in 14 (32%); a Glasgow Coma Scale (GCS) <15 at HEMS arrival was associated independently with NIPPV failure (adjusted odds ratio 13.9; 95% CI, 2.4-80.3; P =.003). Mean scene times were significantly longer in patients who failed NIPPV when compared with patients in whom NIPPV was successful (95 minutes vs 51 minutes; 39.4 minutes longer; 95% CI, 16.2-62.5; P =.001). Conclusion: Patients with a decreased level of consciousness were more likely to fail NIPPV. Furthermore, patients who failed NIPPV had significantly longer scene times. The benefits of NIPPV should be balanced against risks of long scene times by HEMS providers. Knowing risk factors of NIPPV failure could assist HEMS providers to make the safest decision for patients on whether to initiate NIPPV or proceed directly to endotracheal intubation prior to transport. JS Lee, D O'Dochartaigh, M MacKenzie, D Hudson, S Couperthwaite, C Villa-Roel, BH Rowe .Factors associated with failure of non-invasive positive pressure ventilation in a critical care helicopter Emergency Medical Service .Prehosp Disaster Med 2015 ;30 (2 ):1 –5